Evaluation of Self-efficacy and Confidence Levels Among Newly Graduated Nurses Exposed to an End-of-Life Simulation: A Comparison Study. Issue 6 (December 2020) - Edwards, Catherine; Hardin-Pierce, Melanie; Anderson, Debra; Rexford, Tracy
Abstract : Self-efficacy and confidence levels among newly graduated nurses who participated in an end-of-life simulation were compared with nurses who had been practicing for no more than a year but had not participated in an end-of-life simulation. The study included a pretest-and-posttest evaluation of an end-of-life simulation intervention during a new graduate residency program among newly graduated nurses to improve self-efficacy and confidence with end-of-life care. Nurses who had been in practice for no more than a year but had not been exposed to an end-of-life simulation intervention were also surveyed. The Palliative Care Evaluation Tool Kit was adapted and used for this project. The 2 groups of nurses were compared in terms of self-efficacy and confidence levels regarding end-of-life care. An end-of-life simulation intervention was successful in improving self-efficacy and confidence levels among newly graduated nurses, in regard to views about end of life and death and dying compared with the nurses who did not receive the end-of-life simulation intervention. The results of this study have implications for both schools of nursing and hospital training programs.